THE INVENTION AND REINVENTION OF THE CITY - Koolhaas, Rem (Journal of international affairs (New York), 2012)
In an interview, leading urban theorist and a Pritzker Prize-winning architect Rem Koolhaas discussed how the economic and cultural changes of the twenty-first century and transforming world cities and also the practice of architecture. On whether cities around the world share common challenges, he said that what he sees more than anything is the inability of almost every political system to anticipate, mobilize and take precautions for the future, even when it is obvious that cities will grow or shrink rapidly. It doesn't take particular expertise to deal with these challenges. However, this inability to plan ahead is widespread and it is always shocking when it happens in individual cases. What is now called "green architecture" is an opportunistic caricature of a much deeper consideration of the issues related to sustainability that architecture has been engaged with for many years. It was one of the first professions that was deeply concerned with these issues and that had an intellectual response to them.